Tinjauan Rancangan Undang-Undang Keamanan Nasional Indonesia Dalam Perspektif Menghadapi Masa Depan - Pasaribu, Wempy; Bahri, M. Mossadeq; Hanita, Margaretha; Ghafur, Hanief (Jurnal Keamanan Nasional, 2023)
A large country like Indonesia should have a law on national security, as a basis for law enforcement and national security stability. Views about concerns about military domination or civilian fear of the abuse of authority by the articles of the National Security Law by the Police, it is time to eliminate them with the formulation of firm and precise articles in the National Security Bill and authorization of prosecution. It is time to emphasize the use of the words ‘leading sector’ with the term involvement and taking over authority in dealing with escalating threats that endanger National Security (Kamnas) and state sovereignty. Every potential threat, both from outside and from within the country, should be seen as a serious threat and handled together for the sake of the integrity and stability of the country’s security. It is time to determine the rules of engagement in each escalation of threats, and the authority of the agencies involved, as well as the authorization of officials who have the right to determine the escalation and involvement of agencies.